Development Strategy of Leading Agricultural Commodities: Findings From LQ, GRM, and Shift-Share Analysis - Marina, Ida; Mukhlis, Mukhlis; Oksifa Rahma Harti, Adi (Jurnal Penelitian Pertanian Terapan, 2024)
This research aims to develop the potential of food crops as a first step in the development planning process. This research was conducted in Majalengka Regency and has resulted in three main studies. First, it identifies staple and non-staple food crops in the region. The data source used consists of time series data from 2018-2022, and primary data with sample determination using the Proportional Random Sampling method. The results of the analysis show that staple food crops in Kabupaten M consist of rice, corn, soybeans, peanuts and green beans, while non-staple food crops include cassava and sweet potatoes. Secondly, the study also indicated that rice is the main food crop in the region. Finally, maize and groundnuts were identified as priority crops for further development. These findings provide valuable information for agricultural development planning, focusing on the development of potential commodities.